APPLICATION DESIGN GEOGRAPHIC INFORMATION SYSTEM OF FLOOD LOADING MAPPING IN TULUNGAGUNG REGENCY REGION - Mohammad Panji Romadhoni (Universitas Islam Balitar, 2018)
Tulungagung Regency has a history of experiencing floods, which damaged infrastructure and claimed lives in Tulungagung Regency due to the lack of facilities, knowledge and initial handling of flood disasters to be one of the contributing factors. This study uses primary data and secondary data in the form of slope data, soil type and rainfall. The results of the analysis obtained the level of flood vulnerability in the Tulungagung district area resulting in three levels of classes, namely vulnerability is very vulnerable, vulnerable, and not vulnerable. Making the system using ArcMap PHP web programming and using the MySQL database offline. To process map data used GIS tools (geographic information system), namely the spatial analysis tool of flood hazard level with a visual mapping model. The results of this study are expected to be useful in providing information on flood-prone areas in Tulungagung Regency and it is hoped that the Tulungagung Regency government and the private sector will routinely conduct disaster socialization, especially for communities in flood-prone areas.